2000
DOI: 10.1001/archneur.57.3.333
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of the DYT1 Mutation in Primary Torsion Dystonia Without Family History

Abstract: For accurate diagnosis and genetic counseling, screening for the DYT1 deletion is of great interest in cases with generalized dystonia without a family history. In other cases, positive results are rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 9 publications
3
16
2
Order By: Relevance
“…Patients with generalized dystonia are underrepresented in our study,possibly because these cases are mostly reported to neuropediatricians. However, our data are far below the frequency of the DYT1 mutation observed in other studies [1,8,17].Valente et al [17] found the DYT1 mutation in 60 % of European PTD patients with the typical DYT1 phenotype, suggesting that those who do not carry the mutation (40 %) may represent either allelic or locus heterogeneity in dystonia. In another study of patients with similar Slav ethnic background the GAG deletion was identified in 8 out of 15 Russian families (53 %) with the typical early-onset generalized dystonia [15].…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Patients with generalized dystonia are underrepresented in our study,possibly because these cases are mostly reported to neuropediatricians. However, our data are far below the frequency of the DYT1 mutation observed in other studies [1,8,17].Valente et al [17] found the DYT1 mutation in 60 % of European PTD patients with the typical DYT1 phenotype, suggesting that those who do not carry the mutation (40 %) may represent either allelic or locus heterogeneity in dystonia. In another study of patients with similar Slav ethnic background the GAG deletion was identified in 8 out of 15 Russian families (53 %) with the typical early-onset generalized dystonia [15].…”
Section: Discussioncontrasting
confidence: 74%
“…Our Case 2, with segmental dystonia affecting both arms and the laryngeal region, without any progression in the course over 10 years and no new affected parts of the body for almost 18 years, is similar to cases in the family of Patient 3 described by Valente et al [17], who had segmental dystonia affecting only the arms, but without craniocervical involvement. Cases of the DYT1 mutation with a segmental phenotype have been rarely reported [1]. Gasser et al [6] described a family with 5 clinically affected members carrying this mutation in whom the disease presented as a dystonic writer's cramp during late childhood or adolescence, which affected sequentially both sides but did not progress further.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Apparently sporadic cases because of the low penetrance have also been reported earlier. 20 The difficulties in genetic counselling concerning dystonia is partly due to the low penetrance of many of the hereditary forms of dystonia and partly due to the variable phenotype within the same type of dystonia and, as shown in our study, the occurrence of de novo mutations.…”
Section: Discussionmentioning
confidence: 57%
“…Direct analysis of known dystonia genes may require a significant amount of laborators work and has variable costs, depending on the number of known mutations and the size of the gene tested. For example, testing of the DYT1 mutations is simple and inexpensive; by contrast, analysis of the DYT5 gene is time consuming and expensive.A common feature of all primary dystonia genes so far identified is the reduced penetrance, that never exceeds 40 % [48,49]. This means that the status of asymptomatic dystonia gene carrier is more likely than that of affected carrier.…”
Section: Supportive Laboratory Examinationsmentioning
confidence: 99%